Concise synthesis of moracin M using Appel mediated dehydration of a bioinspired endoperoxide. (12th January 2023) - Al-Jawaheri, Yassir; Elsegood, Mark R.J.; Mistry, Jai-Ram; Kimber, Marc C.
Graphical abstract: Abstract: A synthesis of moracin M using Appel dehydration of a biomimetic inspired endoperoxide and subsequent late stage aromatization, is described. A key 1, 3-diene, obtained from a base-free Suzuki-Miyaura coupling, can undergo biomimetic oxidation to its endoperoxide, followed by dehydration under Appel conditions and aromatization to give a benzofuran, with subsequent deprotection then providing moracin M in only 4-steps. Alternatively, this 1, 3‑diene can undergo aromatization and subsequent deprotection providing a synthetic route to resveratrol.